Nepremoženjska škoda zaradi posega v pravico do zdravega življenjskega okolja - Možina, Damjan (Podjetje in delo, 2016)
The paper presents the jurisprudence of the courts in Slovenia about the liability of the state for loss due to the noise from public roads. The courts have upheld thousands of individual claims for the recovery of non-pecuniary loss for mental suffering due to infringement of the constitutional right to a healthy environment (Art. 72 of the Slovenian Constitution), which is considered a personality right. Particular aspects of this case law are presented together with the relevant case law of the ECHR. The author is critical about Slovenian case law. In his view, the automatic transfer of the principles of private law (such as with regard to immissions) to the relations with the state is not appropriate. A balance between the public and individual interests should be sought. The economic capability of the state to pay massive damages should be considered as well. Upholding claims in full amount to the individuals who did nothing to prevent the noise (e.g. instalment of sound proof windows) is not appropriate. The problem should be dealt with by way of analogy to the (partial) expropriation in public interest. A state should not be overburdened with damages claims.
Keywords: človekove pravice; človekovo okolje; država; hrup; nepremoženjska škoda; odškodninska odgovornost; onesnaževanje okolja